IMPROVING STUDENTS’ SPEAKING SKILL BY MIND MAPPING STRATEGY - Sulastri Sulastri (Language-Edu, 2020)
This research anxieties with the mind mapping be implemented to improve the speaking skill of the students of Mentari class in elementary level at Fajar English course. In addition, the purposes of this research are to describe how mind mapping can be implemented to improve the speaking skill of the students of Mentari class in elementary level at Fajar English course. This research used Classroom Action Research. This research aimed to apply a strategy to help the students learning to speak effectively. Classroom action research is a research action that uses a specific strategy, uses significant teacher observations and has certain research rules. Likewise, researcher used questionnaires and interviews as instruments. Based on the result of data analysis, the researcher can conclude that in two research cycles, the researcher found strategies to solve problems in the speaking class, such as: brainstorming before starting teaching; show students examples of mind mapping; demonstrate how to make mind mapping, use pictures as initial ideas, use colors, use lines as a connecting topic; Explanation that mind mapping is a visual display of ideas. Branches of sub topics spread from ideas of thought; provide student paper for making mind maps; asking students to say words in mind mapping; asking the students to make paragraph from the topic and apply in mind mapping; giving the students a chance to speak base on mind mapping orally; asking the students to speak up based on mind mapping. The second, the technique was more effective to help them to improve talking. This was proven by the result of the observation checklist, analysis guide of the teacher, questioner, and the students’ score often in the two cycles raised than preliminary study scores. Those scores were no one get 75 (previous score), 17 students or 70% got under 75 score or 8 students’ or 30% passed the minimum started achievement 75 (in cycle 1), and 20 students or 80% passed the minimum standard achievement, 75 (in cycle 2). This research has reached the criteria for success.Keywords: Extensive reading, Independent learning